Effect of nanoscale TiO 2 -activated carbon composite on Solanum lycopersicum (L.) and Vigna radiata (L.) seeds germination - Singh P.; Singh R.; Borthakur A.; Srivastava P.; Srivastava N.; Tiwary D.; Mishra P.K. (My University, 2025)
The extensive use of nanoparticles under different industrial processes and their release into the environment are of major concerns in the present global scenario. In the present study, the effects of activated carbon-based TiO 2 (AC-TiO 2 ) nano-composite on the seed germination of Solanum lycopersicum (tomato) and Vigna radiata (mungbean) were investigated. The size of nanoparticles used in the study ranged from 30 to 50 nm, and their concentrations were from 0 to 500 mg L −1 . The composites were synthesized by sol–gel method and further characterized by scanning electron microscopy, Energy-dispersive X-rays spectroscopy (EDX), Raman spectroscopy, Fourier transform infrared spectroscopy and X-ray diffraction to investigate all the surface structural and chemical properties of AC-TiO 2 nano-composite. The results showed that increase in nano-composite concentration improves the germination rate and reduces germination time up to a certain concentration. Therefore, employing AC-TiO 2 nano-composites in suitable concentration may promote the seed germination and also reduce the germination time in Solanum lycopersicum and Vigna radiata. Further, it may help to understand the interface of TiO 2 nanoparticles with the environment and agriculture before its application to the field. © 2016, Joint Center on Global Change and Earth System Science of the University of Maryland and Beijing Normal University and Springer-Verlag Berlin Heidelberg.